Study of prevalence of anemia among pregnant women attending antenatal checkup in a rural teaching hospital in Telangana, India - ., Shridevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anemia during pregnancy is a major cause of morbidity and mortality in pregnant women in developing countries and has both maternal and fetal consequences. The objective of the present study was to evaluate the prevalence of anemia among pregnant women attending antenatal checkup in a rural teaching hospital in Telangana. Methods: It is a hospital based cross-sectional observational study conducted in the department of Obstetrics and Gynecology at Maheshwara Medical College and Hospital, Telangana for duration of two years from March 2016 to April 2018. A total of 600 cases were studied and screened. Prevalence of anemia was calculated. Anemia was classified morphologically based on peripheral smear findings and classified as microcytic hypochromic, macrocytic, dimorphic anemia, normocytic normochromic anemia and normocytic hypochromic anemia. Based on hemoglobin values anemia was classified into mild, moderate, and severe anemia. Results: Prevalence of anemia in pregnancy in rural Telangana was about 20%. Age-wise, majority (58.3%) of the patients were between 21 to 25 years. Gravida more than 2 were more 66.6% (400/600) when compared to lower parity. Among 600 cases, 140 pregnant women (23.3%) suffered with mild anemia, 340 cases (56.6%) with moderate anemia and 20% with severe anaemia. Morphologically, microcytic hypochromic type i.e., iron deficiency anaemia was the most common. Conclusions: Anemia in pregnancy in rural Telangana is quite high and was found to be 20% in routine antenatal outpatient cases. Multiple pregnancies and low level of education indirectly contribute to anemia of pregnancy. Education and awareness about anemia in pregnancy can lead to better fetal and maternal outcomes.